Bone repair material with long-acting anti-inflammatory function and preparation method thereof
By using anti-inflammatory drug core materials in bone repair materials to coat them in polylactic acid microcapsule structures and combining biodegradable inorganic substances, the problem of traditional bone repair materials triggering inflammatory tissue reactions in the later stage of degradation is solved, and a long-term Effective anti-inflammatory function and bone growth promotion effect.
Patent Information
- Application Number
- CN202411404309.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional bone repair materials are prone to trigger inflammatory tissue reactions in the later stages of degradation, and existing drug-loaded microspheres cannot control the speed of drug delivery, resulting in uneven drug release.
The bone repair material wrapped in the polylactic acid microcapsule structure is used with an anti-inflammatory drug core material, and a second wall material composed of biodegradable inorganic substances is combined to delay the degradation of the material and the release of drugs.
It realizes long-term anti-inflammatory function, extends the anti-inflammatory effect of the material to 28 days, reduces the risk of inflammation, and promotes bone growth to adapt to the needs of different patients.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical materials, and specifically relates to a bone repair material with long-acting anti-inflammatory function and a preparation method thereof. Background Art
[0002] Bone defects can be caused by a variety of factors, such as trauma, tumors, infection, osteoporosis, etc. These defects not only cause pain and dysfunction, but also lead to complications such as fractures, deformities, infections, and arthritis. Traditional surgical repair methods include autologous or allogeneic bone transplantation to fill the defect, but there are problems such as long postoperative recovery time, difficulty in donor matching, and risk of pathogen transmission. The metal implants currently used in clinical practice also have disadvantages such as poor biocompatibility, implant loosening, and infection. Therefore, the ideal load-bearing bone defect repair scaffold should have good mechanical support capacity, biocompatibility, degradability, and bioinduction and optimization.
[0003] Polylactic acid (PLA) has excellent biodegradability and absorbability, as well as good biocompatibility, non-toxicity, and good capsule and film-forming properties, so it has good application prospects in the field of bone repair. PLA belongs to aliphatic polyesters. The principle of its degradation is that the random hydrolysis of ester bonds leads to molecular chain breakage, which degrades into lactic acid and glycolic acid in the human body and is finally metabolized into products C02 and H20. However, as a bone repair material, polylactic acid is prone to induce delayed non-infectious inflammatory tissue reactions in the later stage of its implantation, so the method of loading anti-inflammatory drugs is generally used to solve this problem.
[0004] A Chinese patent (CN201910618008.7, authorization announcement date: August 12, 2022) discloses a method for preparing magnesium-doped hydroxyapatite drug-loaded microspheres. The invention uses calcium-rich shells as the main raw material, and uses hydrothermal synthesis technology combined with sodium citrate chelating agent to prepare magnesium-doped hydroxyapatite microspheres and load anti-tumor and pro-repair drugs. The microspheres can ensure a large drug loading rate through their porous structure, but the drug-loaded microspheres cannot control the drug supply speed. There may be an oversupply of drugs in the early stage of placement, and no drugs can be supplied in the later stage. Continuous and effective drug supply cannot be guaranteed, so it still cannot be promoted on a large scale.
[0005] Chinese patent (CN201410838299.8, authorization announcement date: January 4, 2017) discloses a polylactic acid composite material that promotes bone growth and biocompatibility and a preparation method, using polylactic acid and pearl powder as raw materials, and obtaining a polylactic acid composite material modified with pearl powder after solvent dissolution, magnetic stirring, ultrasonic dispersion, solvent volatilization and removal. Although the material is introduced into simulated body fluid and hydroxyapatite can be grown on the material using bionic calcification technology, the acidic toxic small molecules produced after the degradation of polylactic acid are prone to produce aseptic inflammation, which is not conducive to cell growth and adhesion. Summary of the invention
[0006] In order to solve the problems existing in the prior art, the technical solution provided by the present invention is:
[0007] The bone repair material with long-acting anti-inflammatory function provided by the present invention comprises a core material composed of anti-inflammatory drugs, a first wall material composed of biodegradable polymers, and a second wall material composed of biodegradable inorganic substances. The anti-inflammatory drug core material is coated in a microcapsule structure with polylactic acid as the first wall material, the weight ratio of the core material to the first wall material is 0.01 to 0.1:1, and the weight ratio of the first wall material to the second wall material is 2:1 to 3:1.
[0008] The method for preparing the bone repair material with long-term anti-inflammatory function comprises the following steps:
[0009] S1: Preparation of polylactic acid: Dehydrate the lactic acid raw material at 110-140° C. for 5-8 hours to obtain lactic acid oligomers, add any one of tin chloride, stannous chloride and stannous lactate as a catalyst to the lactic acid oligomers at 100-120° C. under inert atmosphere protection and stir for 1-3 hours, continue to heat to 160-200° C., and polycondense under vacuum for 10-20 hours to obtain polylactic acid;
[0010] S2: Add any one of acetone, ethanol, and dioxane as an organic solvent to the polylactic acid obtained in step S1, stir thoroughly for 1-3 hours, and then add any one of fatty acid sorbitan, polysorbate, and poloxamer as an emulsifier and continue stirring to obtain a stable emulsion R2;
[0011] S3: dissolving the anti-inflammatory drug in water to obtain solution L3, adding solution L3 dropwise to emulsion R2, and continuing stirring at 60-70° C. for 1-2 h to obtain emulsion R3;
[0012] S4: fully mix any one of KH-560 silane coupling agent, B-201 silane coupling agent, and VTPS silane coupling agent with the second wall material in a ratio of 1:6-10, add the mixture into the emulsion R3, stir for 3-8h at 50-70°C, and evaporate the organic solvent by reduced pressure distillation to obtain slurry R4;
[0013] S5: After the organic solvent is evaporated from S4, the slurry R4 is freeze-dried for 12-48 hours to obtain a bone repair material with long-term anti-inflammatory function.
[0014] Preferably, the anti-inflammatory drug used as the core material is one or more combinations of doxorubicin, doxorubicin hydrochloride, curcumin, cyclophosphamide, bleomycin, meloxicam, celecoxib, nimesulide and etoricoxib.
[0015] Preferably, the biodegradable polymer used as the first wall material is polylactic acid.
[0016] Preferably, the biodegradable inorganic substance used as the second wall material is at least one of nano tricalcium phosphate, nano hydroxyapatite and nano calcium silicate.
[0017] Compared with the prior art, the present invention has the following advantages: 1. The present invention uses polylactic acid as the first wall material to wrap the anti-inflammatory drug core material, and at the same time uses a second wall material composed of biodegradable inorganic substances, which delays the degradation of polylactic acid and the release of anti-inflammatory drugs. It still has a good anti-inflammatory effect after 28 days to meet the needs of different patients and can effectively solve the inflammation problem that occurs in the late stage of polylactic acid degradation: 2. The second wall material composed of biodegradable inorganic substances is coated on the outside of the first wall material composed of polylactic acid, which can be used as a bone growth factor, especially nano-hydroxyapatite has better biological activity, is more conducive to the growth of osteoblasts, and can reduce the cost of bone repair; 3. The present invention directly prepares an anti-inflammatory material with a core-shell structure through the synthesized polylactic acid, omitting some high-energy consumption processes such as drying. The preparation method of the bone repair material provided has the advantages of simple process, easy availability of materials, obvious effect, etc., and has good application prospects and market prospects. DETAILED DESCRIPTION
[0018] Next, embodiments of the present invention will be described.
[0019] Embodiment 1:
[0020] The lactic acid raw material was dehydrated at 110°C for 8 hours to obtain lactic acid oligomers, and the lactic acid oligomers were stirred for 1 hour by adding tin chloride catalyst at 120°C under argon protection, and then the temperature was continued to rise to 200°C, and polycondensed under vacuum conditions for 10 hours to obtain polylactic acid. The above polylactic acid was fully stirred in acetone for 1 hour, and then fatty acid sorbitan was added thereto to obtain a stable emulsion R12. Doxorubicin was dissolved in water, and the doxorubicin aqueous solution was added dropwise to the above emulsion R12, and fully stirred at 60°C for 1 hour to obtain a stable emulsion R13, wherein the weight ratio of doxorubicin to polylactic acid was 8:100. After the KH-560 silane coupling agent and nano-tricalcium phosphate were fully mixed at a weight ratio of 1:7, they were added to the emulsion R13, and continued to stir at 55°C for 5 hours, and the organic solvent was evaporated by reduced pressure distillation to obtain a slurry, and the slurry was frozen for 24 hours to obtain a bone repair material M1 with long-term anti-inflammatory function.
[0021] Embodiment 2:
[0022] The lactic acid raw material was dehydrated at 120°C for 6 hours to obtain lactic acid oligomers, and the lactic acid oligomers were stirred for 2 hours by adding stannous lactate catalyst under argon protection at 130°C, and then the temperature was continued to rise to 190°C, and polycondensed under vacuum conditions for 15 hours to obtain polylactic acid. The above polylactic acid was fully stirred in dioxane for 3 hours, and then polysorbate was added thereto to obtain a stable emulsion R22. Doxorubicin hydrochloride was dissolved in water, and the doxorubicin hydrochloride aqueous solution was added dropwise to the above emulsion R22, and fully stirred at 70°C for 1 hour to obtain a stable emulsion R23, wherein the weight ratio of doxorubicin hydrochloride to polylactic acid was 1:10. After the VTPS silane coupling agent and nano-hydroxyapatite were fully mixed at a weight ratio of 1:9, they were added to the emulsion R23, and continued to stir at 60°C for 5 hours, and the organic solvent was evaporated by reduced pressure distillation to obtain a slurry, and the slurry was frozen for 36 hours to obtain a bone repair material M2 with long-term anti-inflammatory function.
[0023] Embodiment 3:
[0024] The lactic acid raw material was dehydrated at 130°C for 8 hours to obtain lactic acid oligomers, and the lactic acid oligomers were stirred for 3 hours by adding stannous chloride catalyst at 100°C under argon protection, and then the temperature was continued to rise to 180°C, and polycondensed under vacuum conditions for 14 hours to obtain polylactic acid. The above polylactic acid was fully stirred in ethanol for 3 hours, and poloxamer was added thereto to obtain a stable emulsion R32. Curcumin was dissolved in water, and the curcumin aqueous solution was added dropwise to the above emulsion R32, and fully stirred at 70°C for 1 hour to obtain a stable emulsion R33, wherein the weight ratio of curcumin to polylactic acid was 1:6. After the VTPS silane coupling agent and nano calcium silicate were fully mixed at a weight ratio of 1:6, they were added to the emulsion R33, and continued to stir at 65°C for 5 hours, and the organic solvent was evaporated by reduced pressure distillation to obtain a slurry, and the slurry was frozen for 36 hours to obtain a bone repair material M3 with long-term anti-inflammatory function.
[0025] Embodiment 4:
[0026] The lactic acid raw material was dehydrated at 140°C for 5 hours to obtain lactic acid oligomers, and the lactic acid oligomers were stirred for 3 hours by adding tin chloride catalyst at 110°C under argon protection, and then the temperature was continued to rise to 200°C, and polycondensed under vacuum conditions for 20 hours to obtain polylactic acid. The above polylactic acid was fully stirred in acetone for 3 hours, and then fatty acid sorbitan was added thereto to obtain a stable emulsion R42. Cyclophosphamide was dissolved in water, and the cyclophosphamide aqueous solution was added dropwise to the above emulsion R42, and fully stirred at 70°C for 1 hour to obtain a stable emulsion R43, wherein the weight ratio of cyclophosphamide to polylactic acid was 1:6. After the KH560 silane coupling agent and nano calcium silicate were fully mixed at a weight ratio of 1:8, they were added to the emulsion R43, and continued to stir at 70°C for 3 hours, and the organic solvent was evaporated by reduced pressure distillation to obtain a slurry, and the slurry was frozen for 36 hours to obtain a bone repair material M4 with long-term anti-inflammatory function.
[0027] Embodiment 5:
[0028] The lactic acid raw material was dehydrated at 110°C for 8 hours to obtain lactic acid oligomers, and the lactic acid oligomers were stirred for 2 hours by adding stannous lactate catalyst under argon protection at 120°C, and then the temperature was continued to rise to 200°C, and polycondensed under vacuum conditions for 12 hours to obtain polylactic acid. The above polylactic acid was fully stirred in ethanol for 3 hours, and then polysorbate was added thereto to obtain a stable emulsion R52. Bleomycin was dissolved in water, and the bleomycin aqueous solution was added dropwise to the above emulsion R52, and fully stirred at 70°C for 1 hour to obtain a stable emulsion R53, wherein the weight ratio of bleomycin to polylactic acid was 1:8. B-201 silane coupling agent and nano-hydroxyapatite were fully mixed in a weight ratio of 1:9, and then added to emulsion R53, and continued to stir at 70°C for 3 hours, and the organic solvent was evaporated by reduced pressure distillation to obtain a slurry, and the slurry was frozen for 48 hours to obtain a bone repair material M5 with long-term anti-inflammatory function.
[0029] Embodiment 6:
[0030] The lactic acid raw material was dehydrated at 130°C for 6 hours to obtain lactic acid oligomers, and the lactic acid oligomers were stirred for 2 hours by adding stannous chloride catalyst at 110°C under argon protection, and then the temperature was continued to rise to 180°C, and polycondensed under vacuum conditions for 15 hours to obtain polylactic acid. The above polylactic acid was fully stirred in dioxane for 2 hours, and then fatty acid sorbitan was added thereto to obtain a stable emulsion R62. Bleomycin was dissolved in water, and the bleomycin aqueous solution was added dropwise to the above emulsion R62, and fully stirred at 70°C for 1 hour to obtain a stable emulsion R63, wherein the weight ratio of bleomycin to polylactic acid was 1:8. B-201 silane coupling agent and nano-tricalcium phosphate were fully mixed in a weight ratio of 1:9, and then added to emulsion R63, and continued to stir at 60°C for 3 hours, and the organic solvent was evaporated by reduced pressure distillation to obtain a slurry, and the slurry was frozen for 12 hours to obtain a bone repair material M6 with long-term anti-inflammatory function.
[0031] Pure polylactic acid was used as the control group D1. Mouse embryonic osteoblasts were inoculated onto the surfaces of M1~M6 and D1, and each sample was immersed in simulated blood, and the simulated blood was replaced once a day during the immersion period. The absorbance values at wavelengths of 490nm and 570nm were measured by an ELISA instrument on the 1st, 4th and 7th days. The relative proliferation rate of the control group D1 was set to 100%, and the relative cell proliferation rate of each bone repair material M1~M6 relative to pure polylactic acid was obtained after conversion. The specific results are shown in Tables 1 and 2 below. The results show that the relative cell proliferation rate of the M2 and M5 samples is higher, indicating that nanohydroxyapatite has better biological activity and is more conducive to the growth of mouse embryonic osteoblasts.
[0032] Table 1 Relative cell proliferation rate % (490nm)
[0033] Day 1 Day 4 Day 7 M1 119 134 129 M2 135 157 149 M3 123 149 134 M4 125 150 141 M5 133 161 147 M6 121 137 128 D1 100 100 100
[0034] Table 2 Relative cell proliferation rate % (570nm)
[0035] Day 1 Day 4 Day 7 M1 127 146 139 M2 144 187 173 M3 131 159 148 M4 139 160 153 M5 151 184 177 M6 134 157 149 D1 100 100 100
[0036] Samples M1 to M6 and D1 were immersed in simulated blood, and the simulated blood was replaced once a day during the immersion period. The simulated blood was taken on the 1st, 7th, 14th, 21st, and 28th days to test its antibacterial rate against Escherichia coli and Staphylococcus aureus. The test results showed that the antibacterial rate of comparative example D1 was 0% each time; the antibacterial rate of samples M1 to M6 on the 1st, 7th, and 14th days against Escherichia coli and Staphylococcus aureus could reach 99%; the antibacterial rate of samples M1 to M6 on the 28th day against Escherichia coli and Staphylococcus aureus could reach 85%, indicating that the bone repair material provided by the present invention has good anti-inflammatory function.
[0037] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A bone repair material with long-lasting anti-inflammatory function, characterized in that: Includes the following components: Core material, anti-inflammatory drugs; a first wall material composed of a biodegradable polymer; The second wall material is composed of biodegradable inorganic substances.
2. The bone repair material with long-lasting anti-inflammatory function according to claim 1, characterized in that: The anti-inflammatory drug core material is one or more combinations of doxorubicin, doxorubicin hydrochloride, curcumin, cyclophosphamide, bleomycin, meloxicam, celecoxib, nimesulide and etoricoxib.
3. The bone repair material with long-lasting anti-inflammatory function according to claim 1, characterized in that: The first wall material is polylactic acid.
4. The bone repair material with long-lasting anti-inflammatory function according to claim 1, characterized in that: The second wall material is at least one of nano tricalcium phosphate, nano hydroxyapatite and nano calcium silicate.
5. The bone repair material with long-lasting anti-inflammatory function according to claim 1, characterized in that: The anti-inflammatory drug core material is coated in a microcapsule structure with polylactic acid as the first wall material, and the weight ratio of the core material to the first wall material is 0.01-0.1:
1.
6. The bone repair material with long-lasting anti-inflammatory function according to claim 1, characterized in that: The weight ratio of the first wall material to the second wall material is 2:1 to 3:
1.
7. The method for preparing the bone repair material with long-term anti-inflammatory function according to any one of claims 1 to 6, characterized in that: The steps include: S1: Preparation of polylactic acid: Dehydrate the lactic acid raw material at 110-140° C. for 5-8 hours to obtain lactic acid oligomers, add a catalyst to the lactic acid oligomers at 100-120° C. under inert atmosphere protection and stir for 1-3 hours, continue to heat to 160-200° C., and polycondense under vacuum for 10-20 hours to obtain polylactic acid; S2: adding an organic solvent to the polylactic acid obtained in step S1, stirring thoroughly for 1-3 hours, and then adding an emulsifier thereto and continuing stirring to obtain a stable emulsion R2; S3: dissolving the anti-inflammatory drug in water to obtain solution L3, adding solution L3 dropwise to emulsion R2, and continuing stirring at 60-70° C. for 1-2 h to obtain emulsion R3; S4: fully mix the silane coupling agent and the second wall material in a ratio of 1:6-10, add the mixture into the emulsion R3, stir for 3-8h at 50-70°C, and evaporate the organic solvent by vacuum distillation to obtain slurry R4; S5: freeze-drying the slurry R4 obtained by evaporating the organic solvent in S4 for 12-48 hours to obtain a bone repair material with long-term anti-inflammatory function; Wherein, the catalyst in S1 is any one of tin chloride, stannous chloride and stannous lactate; The organic solvent in S2 is any one of acetone, ethanol, and dioxane, and the emulsifier is any one of fatty acid sorbitan, polysorbate, and poloxamer; The silane coupling agent in S4 is any one selected from KH-560 silane coupling agent, B-201 silane coupling agent, and VTPS silane coupling agent.
Citation Information
Patent Citations
A polylactic acid composite material for promoting bone growth and biocompatibility and a preparation method thereof
CN104592725B
Preparation method of magnesium-doped hydroxyapatite drug-loaded microsphere
CN110272032A
Cited By
Method for coating Ca-Cur submicron modified material-doped PLA layer on surface of Ag-DCPD film layer
CN121265874A